TinyML and MFCC Feature Extraction for Energy Efficient Automatic Air Purifier Control - Mangasa Manullang; Ferawaty Ferawaty; Leonardo Angkasa; Winson Lim (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Classroom environments are highly susceptible to airborne disease transmission due to high occupant density and prolonged interaction times. Conventional mitigation strategies often rely on continuously operating air purification systems throughout building operational hours. This always-on approach guarantees continuous air circulation but results in massive and unnecessary electrical energy consumption, especially during idle periods or when biological contamination is absent. This research aims to design and implement an energy-efficient smart classroom system that automatically controls air purifiers based on real-time acoustic detection of sneeze events. The system utilizes Tiny Machine Learning embedded on an edge microcontroller with an onboard microphone. Audio datasets comprising sneeze, cough, and speech classes were processed using Mel-Frequency Cepstral Coefficients feature extraction at a 16 kHz sampling rate to optimize memory usage, followed by a neural network classifier training. The hardware prototype controls two air purifiers positioned for cross-ventilation, activating them for 15 minutes exclusively upon sneeze detection. The trained model achieved an overall accuracy of 97.5%, with a perfect precision rate in recognizing sneeze events. Field testing during an active class period demonstrated that the event-driven system consumed only 92.8 Watt-hours. Compared to the conventional continuous operation method, the automated system successfully reduced electrical power consumption by 71.4%. Implementing edge-based artificial intelligence for acoustic environmental monitoring provides a highly reliable approach to automated facility management, balancing health risk mitigation through optimal cross-ventilation with significant electrical energy conservation in smart classrooms. Future integration with low-power wireless modules is highly recommended to transmit event logs to a central dashboard, completing the sustainable facility management ecosystem.